X. Andrade, María Belén Calvache, Liset Coba, Martha Flores, Ángel Emilio Hidalgo, Carlos Tutivén Román y María Pía Vera, Los años viejos, Quito, Fonsal, 2007, 359 pp (Procesos. Revista Ecuatoriana de Historia, 2008)
S.R